Peran modul MP-ASI dalam perilaku pemberian MP-ASI pada ibu anak bawah dua tahun (BADUTA) - SP, Sri Hapsari; Margawati, Ani; Nugraheni, SA. (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2016)
Background  :  Lack  of  complementary feeding behavior is one of the problems in Indonesia. Nutrition education about complementary feeding among mother from infants aged 6-24 months should be carried out to support compelementary feeding behavior. Module with an easily language punctuated by images and can be learned at home is expected to incerase complementary feeding behavior among mothers from child under two years old.Method : The design of this research was quasi-experimental with non-randomized pre-test and post-test  control  group  design. Training of complementary feedings module were given for four meetings. The annalyze were conducted by SPSS program.  Result  : This study found that the median age of subjects between two group are adults. The median duration of education are 9 years. There was no difference of Financial families outcome in the both of groups is low. Nutrition education with module can increase complementary feeding behavior at intervention group  and the improvement of this scores better than control group. Complementary feeding behavior retention increased significant  among 2 weeks and 1 month after intervention.Conclusion : Nutrition education with module contribute to improve complementary feeding behavior among mothers from child under two years old.